Fourth dimension during the use of the bioecotoximonitor in aquatic ecotoxicology - Argota-Pérez, George (2024)
The objective of the study was to describe the fourth dimension in the use of bioecotoxic monitors in aquatic ecotoxicology. Between January and June 2024, a methodology was designed that integrated four dimensions into the analysis: three spatial (length, width, and depth) and one temporal (time), to assess the effects of pollutants on aquatic ecosystems. The results showed that each dimension, by considering the distribution of pollutants and their effects at different depths and over time, provides a detailed and holistic view of environmental health. The spatial dimension allows for the identification of critical contamination hotspots, while the temporal dimension offers insight into seasonal variability and long-term trends. The discussion highlighted that the combination of spatial and temporal dimensions is crucial for a comprehensive evaluation, enabling the detection of seasonal patterns and differences in acute and chronic toxicity. However, the lack of extended monitoring limits the complete identification of these patterns. It is concluded that the integration of these dimensions significantly enhances the capability of bioecotoxic monitors to provide a precise and dynamic assessment of aquatic ecosystems, facilitating more effective environmental management strategies.